PENGARUH SIZE, PROFITABILITAS LEVERAGE DAN UMUR TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi Empiris Perusahaan Manufaktur yang Listing di BEI TAHUN 2010 – 2013) - Sunaryo, Bustan Arya; Mahfud, M. Kholiq (Diponegoro Journal of Management, 2016)
Factors thought to affect the disclosure of corporate social responsibility (CSR) is the company size, profitability, leverage and age. However, based on the results of previous studies showed different results depending on the influence of these variables on disclosure of corporate social responsibility (CSR). The purpose of this study was to analyze the effect of firm size, profitability, leverage and age on the disclosure of corporate social responsibility (CSR). The sample used in this study were 75 companies listed on the Stock Exchange and its shares are actively traded during the period 2010-2013 by using purposive sampling technique. The data used is secondary data. The analysis technique used is multiple linear regression. According to analysis done can be seen that the size of the company does not affect the disclosure of corporate social responsibility (CSR), the profitability of a positive effect on social responsibility disclosure (CSR), leverage significant negative effect on the disclosure of corporate social responsibility (CSR) and the age of the company is not affect the disclosure of social responsibility (CSR). Test results of multiple linear regression showed that the regression model is used to predict good for the disclosure of social responsibility (CSR). While the disclosure of corporate social responsibility (CSR) can be explained by the independent variables are firm size, profitability, leverage and age of 20.1%.